Do Teachers' College Majors Affect Students' Academic Achievement in the Sciences? A Cross-Subfields Analysis with Student-Teacher Fixed Effects - Atsushi Inoue; Ryuichi Tanaka (Institute of Labor Economics (IZA), 2022)
We examine whether and how teachers' major fields of study affect students' achievement, exploiting within-student variation across subfields in natural science (i.e., physics, chemistry, biology, and Earth science). Using middle-school students' data from the Trends in International Mathematics and Science Study and controlling student-teacher fixed effects, we find that teachers with college majors in natural sciences improve students' achievement of subfields in natural sciences corresponding to their subfields of college majors. Teaching practices explain about half of the effect of teachers' major fields. Most of the effects of teaching practices are accounted for by teachers' preparation for teaching science topics. The results are robust to potential endogenous matching between students and teachers.
Keywords: H75; I21; J24; 330; education; teacher; natural science; college major; middle school; TIMSS